Carbonate diagenesis in the Barremian-Aptian Tirgan Formation (Kopet-Dagh Basin, NE Iran): Petrographic, geochemical and reservoir quality constraints. (August 2018) - Javanbakht, M.; Wanas, H.A.; Jafarian, A.; Shahsavan, N.; Sahraeyan, M.
Abstract: This study aims to establish the diagenetic evolution of carbonate rocks of the Barremian-Aptian Tirgan Formation (Kopet-Dagh Basin, NE Iran), with special emphasis in their impact on reservoir quality to be used as analog for their equivalent carbonate reservoirs. To achieve this target, basic petrography complemented by elemental and stable isotopic (δ 18 O and δ 13 C) analyses of the studied carbonate rocks was used. In addition, the visible porosity was detected. The recognized carbonate diagenetic processes include micritization, cementation, dolomitization, compaction, dissolution, stylolitization, fracturing, silicification and neomorphism. These diagenetic processes took place in four diagenetic environments: marine-phreatic, meteoric-phreatic, meteoric-vadose and burial. Early dolomitization of lime muds, micritization of skeletal allochems and cementation by isopachous equant calcite represent marine-phreatic diagenesis. The meteoric-phreatic diagenesis was accompanied with the development of granular non-ferroan calcite cement, neomorphosed carbonate matrix and recrystallized bioclasts. The meteoric-vadose diagenesis led to prevalence of dissolution process and sparry calcite infilling the fractures. Late dolomitization, ferroan blocky and poikilotopic calcite cement, stylolitization and silicification processes were developed during burial diagenesis. An integration of the petrographic study with the geochemical analysis confirms that the studied carbonate rocks were originally composed of aragonite, which was eventually recrystallized to calcite and replaced by dolomite during diagenesis. In terms of reservoir quality, the recognized diagenetic alterations and visible porosities show that the diagenetic processes have a direct effect on modification of both inter- and intra-granular/crystalline porosity. In this manner, it is found that the calcite cementation, micritization and compaction decline the pore spaces, whereas the dolomitization, dissolution, formation of moldic pores and fracturing increase the pore volumes. Consequently, prevalence of dolomitization, dissolution, occurrence of moldic pores and fracturing in the Tirgan carbonate rocks gives the Tirgan Formation and its equivalent rocks a good opportunity to be an excellent reservoirs. Graphical abstract: Highlights: -This study characterizes the diagenetic processes and environments in the carbonate rocks of the Tirgan Formation. Basic petrography in conjunction with various geochemical proxies has been used. Marine-phreatic, meteoric-phreatic, meteoric-vadose and burial diagenesis have been suggested. The recorded diagenetic alterations indicate a high impact on reservoir quality.